Linguistic Hegemony and the Erosion of Local Languages: Analysis of Arab–French Domination to Amazigh Existence in Morocco - Aidatul Fitriyah (Sinergi International Journal of Communication Sciences, 2025)
This research examines how Arabic and French historical and contemporary dominance influences intergenerational communication practices in Amazigh in rural Moroccan communities. The Amazigh language, historically the main marker of the Berber community's collective identity, now faces structural and symbolic pressures from state linguistic policies and social representations that privilege the dominant language. This research uses a literature-based qualitative approach with thematic analysis methods on policy documents, legal products, and institutional and media discourse related to the position of the Amazigh language. The analysis results show that the dominance of Arabic and French impacts not only institutional domains such as education, bureaucracy and the media, but also weakens intergenerational linguistic transmission and creates identity distortions among the younger generation of Amazighs. The Amazigh language is slowly being shifted from its public communicative and cultural symbolic function, becoming a domestic language that lacks legitimacy in the national social system. The absence of substantive policy implementation exacerbates this process of marginalization despite constitutional recognition since 2011. In conclusion, linguistic dominance in Morocco's postcolonial context has created communication disruption and an identity crisis within the Amazigh community. Therefore, revitalizing the Amazigh language requires a legal-formal, community-based, and intergenerational approach. This study provides a theoretical and practical basis for a more inclusive language policy, strengthening postcolonial sociolinguistic discourse in the Maghreb region.